Aran knits : 23 contemporary designs using classic cable patterns - Storey, Martin, 1958- (St. Martin's Griffin, 2012)
"Inspired by traditional fishermen's sweaters from around the British Isles, the 23 classic cable and Aran projects in this book are perfect for knitters who want to experience the delight of creating Aran textures without finding the patterns too complicated to knit."--P. [4] of cover.